Impact of Teachers’ Behavior on Students’ Motivation and Learning at Elementary School Level in Tehsil Jampur District Rajanpur (Al-Qamar, 2024)
This research was conducted to investigate the “impact of teachers’ behavior on students’ motivation and learning at the elementary school level." Teachers behave well to create a positive and supportive classroom learning environment. Teachers’ conduct can influence students’ motivation and learning in many ways. The objectives of the study were: 1) to identify the impact of teachers’ behavior on students’ motivation; and 2) to identify the impact of teachers’ behavior on students’ learning. The nature of the study was a mixed-methods design. The study was limited to the district of Rajanpur, male elementary schools, 6th, 7th, and 8th grades only. The target population of the study was all the elementary public school’s teachers and students in the district of Rajanpur. The sample of the study was 433 elementary school male students and 10 elementary school male teachers. The respondents were selected through a simple random sampling technique. A self-developed, closed-ended questionnaire for students and an interview protocol for teachers were developed by the researcher. The questionnaire and interview were finalized after conducting a pilot test. The students’ questionnaire was designed on a five-point Likert scale. The Cronbach alpha reliability was 0.885. The data was collected, organized, tabulated, and analyzed using percentage, mean, standard deviation, chi square, and Pearson correlation through SPSS version 29.0. The findings of the study were based on objectives. It was found that teachers positive and friendly behavior at the elementary school level impacted students’ motivation and learning positively. According to the salient conclusion of the study, teachers create an inclusive and positive learning environment through their kind behavior. Most students were more engaged and enthusiastic about their teachers’ cooperative classroom environment. Most of the teachers were well aware of the positive atmosphere in the classroom and provided standard teaching methodologies for elementary students. The study recommended that elementary school-level teachers show kind behavior in the classroom for better academic outcomes for the students. It was recommended that teachers create a positive classroom environment by paying extra attention to their students.
Keywords: Teachers’ Behavior; Students’ Motivation; Students’ Learning